2020
DOI: 10.2174/0929867325666181015145225
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Heart-Brain Axis Protection in Obese Surgical Patients: The Nutrigenomic Approach

Abstract: The number of obese patients undergoing cardiac and noncardiac surgery is rapidly increasing because they are more prone to concomitant diseases, such as diabetes, thrombosis, sleep-disordered breathing, cardiovascular and cerebrovascular disorders. Even if guidelines are already available to manage anesthesia and surgery of obese patients, the assessment of the perioperative morbidity and mortality from heart and brain disorders in morbidly obese surgical patients will be challenging in the next years. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 225 publications
2
2
0
Order By: Relevance
“…Long‐term chronic ischaemia can cause myocardial hibernation, these hibernating myocardial cells typically show a loss of contractile filaments, there are excess glycogen granules in the cytosol, sarcoplasmic reticulum and transverse tubules are lost, 43 also, there are abnormalities in mitochondrial size and shape, reactive myocardial hypertrophy and interstitial fibrosis, which secondary to myocyte loss 44 . We also observed the above changes in HF rats in our study, whereas ECH significantly relieves these changes, as the latest study reported recovery of cardiac function after ischaemic stress may be a feature of myocardial hibernation, 45 the myocardial glycogen level is also measured, the results indicates that there is no significant difference among the three groups, as shown in Figure 7J.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Long‐term chronic ischaemia can cause myocardial hibernation, these hibernating myocardial cells typically show a loss of contractile filaments, there are excess glycogen granules in the cytosol, sarcoplasmic reticulum and transverse tubules are lost, 43 also, there are abnormalities in mitochondrial size and shape, reactive myocardial hypertrophy and interstitial fibrosis, which secondary to myocyte loss 44 . We also observed the above changes in HF rats in our study, whereas ECH significantly relieves these changes, as the latest study reported recovery of cardiac function after ischaemic stress may be a feature of myocardial hibernation, 45 the myocardial glycogen level is also measured, the results indicates that there is no significant difference among the three groups, as shown in Figure 7J.…”
Section: Discussionsupporting
confidence: 74%
“…All *P < .05 versus Ctrl,**P < .01 versus Ctrl; # P < .05 versus ISO, ## P < .01 versus ISO. Error bars represent SD in HF rats in our study, whereas ECH significantly relieves these changes, as the latest study reported recovery of cardiac function after ischaemic stress may be a feature of myocardial hibernation, 45 the myocardial glycogen level is also measured, the results indicates that there is no significant difference among the three groups, as shown in Figure 7J.…”
Section: Ech Up-regulates Protein Expression Of Sirt1 Foxo3a and Msupporting
confidence: 46%
“…Obesity and PS have widespread targets in the body. However, the cardio- and neural systems are especially vulnerable to their acute or chronic adverse effects [[7], [8], [9], [10], [11]]. What is more, affecting one compartment may have negative reverberation on the other, resulting in an altered brain-heart communication.…”
Section: Introductionmentioning
confidence: 99%
“…The association between agent toxicity versus cardioprotection could not be corroborated [37]. Publications a decade later support the notion that surgery is safer in the current era however rates of perioperative major adverse cardiovascular events, are still a significant clinical problem [38,39]. While we have raised the argument for mixed method research guidelines for translational research on health services needs within health clusters, we certainly support others exploring the bedside to bench translational guidelines for efficacious phase-IV research for these issues.…”
Section: What Can We Do Better?mentioning
confidence: 88%